The Epidemic Account of Dengue Fever and Influenza A (H1N1) in Espírito Santo-Brazil Press Media: Similarities and Differences - Cavaca, Aline Guio; dos Santos-Neto, Edson Theodoro; Oliveira, Adauto Emmerich; Antunes, Michele Nacif; Cardoso, Janine Miranda (Tempus – Actas de Saúde Coletiva, 2021)
This study analyzed the dengue and influenza A (H1N1) epidemics in the printed media of Espírito Santo state (ES). All reports from November 2007 to December 2010 were collected from the newspaper A Tribuna. The data collected from the Health Information Systems were quantitatively analyzed as per their editorial characteristics, their date of distribution and the number of reported cases and deaths due to the respective pathologies. Dengue was pinpointed in 1870 articles, 133.641 notifications and 94 deaths in the period. H1N1 was pinpointed in 411 news stories, 519 cases and 15 deaths. There was a significant statistic difference in the representations of dengue and influenza A (H1N1) concerning the cover, the editorials, the editorial space and type of opinionated report. There was a stronger statistical correlation between the number of deaths, notifications and news reports of dengue, when compared to the same correlations for influenza A (H1N1). The number of reported cases directly influences the spread of the news of the diseases studied. Contemporary epidemics are complex events, in which media constructions participate actively, bringing risk perceptions into focus that may exponentially raise tensions and meddle in health policies.